Enhancing Camera Purchasing Decisions: A Multicriteria Decision Support System using the Dempster-Shafer Method - Winiski, Raditya (International Enterprise Integration Association, 2024)
This research explores the development and implications of a Decision Support System (DSS) tailored for assisting consumers and businesses in navigating the complexities of camera purchasing decisions. Leveraging the Dempster-Shafer method, the study establishes a structured framework integrating multiple decision criteria to provide personalized recommendations aligned with user preferences. The research begins by delineating the significance of informed decision-making in camera purchases, acknowledging the intricate interplay between technical specifications, user preferences, and brand considerations. Building upon this premise, the study articulates the methodology employed in designing and implementing the DSS, emphasizing the integration of the Dempster-Shafer method to amalgamate beliefs across diverse criteria. Through a systematic approach, the DSS demonstrates strengths in its comprehensive multicriteria decision support, personalized recommendation generation, and robust handling of uncertainties inherent in decision-making.